2020
DOI: 10.1186/s12909-020-02262-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing comfort level of organ donation competencies among pediatric intensivists in Saudi Arabia: a national survey

Abstract: Background As increasing the number of organ donations presents a global challenge, Saudi Arabia is no different. Intensivists can play a major role in maximizing the organ donation process and minimize the challenges. The purpose of this study was to investigate Saudi pediatric intensivists’ comfort and importance levels of organ donation competencies. Methods We conducted a cross-sectional survey whose sampling frame included 100 p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…Participants had poor knowledge about corneal donation Less than one-third were favorable to postmortem corneal grafts Religion hindered the willingness to donate in about onequarter of the sample Kazzaz and Da'ar [96] Pediatric intensivists (n = 100) from Central, Eastern, Northern, Western, Southern regions Low perceived comfort levels in several organ donation competencies Comfort levels were influenced by the participants' frequency of exposure to donation after brain death, the health sector, and region of practice Participants viewed most of the competencies as important to their practice Low comfort levels with competencies were associated with gaps in knowledge Thirunavukkarasu et al [97] Students (n = 400) from Jouf The most common organ that can be donated are kidneys, blood, heart, and eyes About two-thirds were not aware of SCOT and its activities The government has to promote organ donation to the public The majority were willing to donate their organs Common barriers for organ donation were a lack of knowledge, founded and unfounded fear, and refusal from family members Omran et al [98] Students (n = 352) from Jeddah, Mecca, and Taif Most of the sample had poor knowledge about organ donation Higher knowledge in sixth-year students than second-year students…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants had poor knowledge about corneal donation Less than one-third were favorable to postmortem corneal grafts Religion hindered the willingness to donate in about onequarter of the sample Kazzaz and Da'ar [96] Pediatric intensivists (n = 100) from Central, Eastern, Northern, Western, Southern regions Low perceived comfort levels in several organ donation competencies Comfort levels were influenced by the participants' frequency of exposure to donation after brain death, the health sector, and region of practice Participants viewed most of the competencies as important to their practice Low comfort levels with competencies were associated with gaps in knowledge Thirunavukkarasu et al [97] Students (n = 400) from Jouf The most common organ that can be donated are kidneys, blood, heart, and eyes About two-thirds were not aware of SCOT and its activities The government has to promote organ donation to the public The majority were willing to donate their organs Common barriers for organ donation were a lack of knowledge, founded and unfounded fear, and refusal from family members Omran et al [98] Students (n = 352) from Jeddah, Mecca, and Taif Most of the sample had poor knowledge about organ donation Higher knowledge in sixth-year students than second-year students…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the overall knowledge about organ donation and transplantation varied based on the research objective (i.e., blood, skin, kidney donation). In general, the participants reported insufficient information about organ donation and transplantation [72,75,78,90,91,95,96,102]. The main source of information about organ donation was TV, social media [72,75,77,79,[81][82][83][84]89].…”
Section: Organ Donation and Transplantationmentioning
confidence: 99%
“…This belief was significantly associated with awareness of the Islamic Fatwa on brain death and organ transplantation, as well as knowledge of SCOT's role, but it did not necessarily lead to registration as donors or the inclination to donate organs to friends or family members. Interestingly, the majority of those registered as deceased donors were willing to donate all potential organs, contrasting with the other literature that identifies the kidney as the most frequently donated organ [9,10,[21][22][23][24][25]. This demonstrates a remarkable level of altruism within the Saudi population.…”
Section: Discussionmentioning
confidence: 77%
“…29 This high percentage was consistent with those previously reported in other national studies; a study from four adult ICUs in Saudi Arabia revealed a non-reporting rate of 67%, while 60% of paediatric intensivists expressed low comfort with the referral process. 14 16 Weiss et al investigated intensivists' knowledge, attitudes and reported behaviour in non-referral scenarios; reasons for nonreferral included perceptions of contraindications that would prevent donation and the presence of family distress. 30 The referral of potential donors is mandatory; nonetheless, a system should be set up to ensure compliance with reporting requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Paediatric intensivists in Saudi Arabia express low comfort levels with organ donation after NDD competencies, including offering families the opportunity for donation, referral process to OPOs, consent discussions, and ethical, legal, and religious considerations. 14 Only three-quarters of healthcare providers in adult intensive care units (ICUs) at a tertiary care hospital in Saudi were aware of the hospital donation policy. 15 In 2004, only 33% of adult patients experienced brain death were reported to SCOT.…”
Section: Introductionmentioning
confidence: 99%